PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. GANSAR JAYA - Sudarno, Sudarno; Prasetyo, Indra; Indrawati, Mei (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
The study is to analyze the the influence of leadership style and compensation on employee performance with motivation as an intervening variable in PT. Gansar Jaya. The research method used is quantitative. All employees of PT. Gansar Jaya formed a study group. All 63 employees of PT Gansar Jaya decided on the sample size used in this study. The truth of the premise of this research will be assessed using the partial least squares (PLS) model analysis. Based on the research results, PT. Gansar Jaya's workers perform better under a favorable leadership style and compensation structure. Management attitude and compensation at PT. Gansar Jaya has a positive effect on employee morale. Statistically significant positive effect of PT. Gansar Jaya on employee performance has been proven. Motivation has been shown in PT. Gansar Jaya to mediate how leader style impacts team performance. motivation turns out to be a bridge between compensation and performance at PT. Gansar Jaya.